Prediction of pre-eclampsia in early pregnancy using PAPP-A and uterine artery pulsatility index - Pratap, Charu; Thakur, Srishti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim is to study the role of first trimester pregnancy associated plasma protein A (PAPP A) and second trimester uterine artery pulsatility index (PI) in prediction of pre-eclampsia in early pregnancy. Methods: This prospective study conducted at GSVM Medical College, Kanpur from May 2011 to May 2012 included 100 pregnant women. Serum PAPP-A level was determined in the first trimester (8-14 weeks) and uterine artery Doppler was done at 20-25 weeks of gestation. Results: Out of 100 patients 7 developed pre-eclampsia. Mean PAPP-A level in pre eclamptic and normotensive patients were 1.25±1.4 and 2.5±0.5ng/ml respectively. Mean PI level in pre eclamptic and normotensive patients were 1.77±0.28 and 0.96±0.25 respectively. The sensitivity and specificity of PAPP-A at cut off <1.7ng/ml was 71%, 71% respectively. The sensitivity and specificity of pulsatility index at cut off >1.4 was 100% ,94% respectively. Conclusions: Low level of maternal serum PAPP-A at 8-14weeks and high level of uterine artery PI at 22-25 weeks of pregnancy can predict subsequent development of pre-eclampsia.